Improving student learning outcomes using the discovery learning model in the indonesian language learning process - Gianistika, Chika; Firmansyah, Very Sukma (Edukasi, 2023)
Recognizing the paramount importance of fostering effective language learning outcomes among primary school students, this action research aims to enhance the Indonesian language learning outcomes for class II students at SDN Wancimekar I, Kotabaru District, Karawang Regency. This research aims to improve Indonesian language learning outcomes for class II students at SDN Wancimekar I, Kotabaru District, Karawang Regency. This action research was carried out at SDN Wancimekar I, Kotabaru District, Karawang Regency with a research population of 420 students and a sample of 40 class II students. The research was carried out in the first semester of the 2023/2024 academic year starting from July to August 2023. The research method used was Action Research with the implementation of action research consisting of 4 (four) basic stages that are interrelated and continuous, namely (1) planning ( planning), (2) implementation (acting), (3) observation (observing), and (4) reflection (reflecting). From the evaluation test results, it can be seen that there is an increase in students' understanding of the subject matter as shown by student learning results from pre-cycle to cycle II. In the Pre-Cycle, the average student score was only 62 with classical completeness of 25%. In Cycle I, the average student score was 64 with classical completeness of 27%. In cycle II, the average student score was 75.85 with classical completion reaching 75%. This research contributes novelty by not only focusing on the outcomes but also by emphasizing the systematic and iterative nature of the action research process. The structured approach, encompassing planning, implementation, observation, and reflection, provides a replicable model for educators and stakeholders aiming to enhance language learning outcomes in primary education settings